The Effect of Employee Work Ability and Welfare Benefits on Employee Work Performance at PT. Wongso Nusantara Bersatu - Anita Monica Sabrina; Rina Loliyana; Nety Kumalasari; Andi Surya; Armalia Reny WA; M Renandi Ekatama Surya (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
Study This aim For know influence ability Work employees and benefits welfare to performance Work employees at PT. Wongso Nusantara Bersatu, both in a way partial and simultaneous. Achievement Work employee reflect how much productive and effective a employee in operate his duties, which are influenced by various internal factors include ability work and benefits welfare. The research method used is method quantitative. Population in study This is all over PT. Wongso Nusantara Bersatu employees totaling 68 people, and engineering taking sample use total sampling method. Data analysis technique used is analysis multiple linear regression with help SPSS application version 27. Research results show that ability Work employees and benefits welfare in a way partial influential positive and significant to performance Work employees. In simultaneous ability Work employees and benefits welfare influential positive and significant to performance employees. Coefficient value determination (R²) of 58.3% shows that ability Work employees and benefits welfare capable explain variables performance Work employees, while the rest 41.7 % is influenced by other factors that are not investigated in study This.